Assessing the Performance of Simple Contracts Empirically: The Case of Percentage Fees - Simon Loertscher; Andras Niedermayer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2012)
This paper estimates the cost of using simple percentage fees rather than the broker optimal Bayesian mechanism, using data for real estate transactions in Boston in the mid-1990s. This counterfactual analysis shows that interme- diaries using the best percentage fee mechanisms with fees ranging from 5.4% to 7.4% achieve 85% or more of the maximum profit. With the empirically observed 6% fees intermediaries achieve at least 83% of the maximum profit and with an optimally structured linear fee, they achieve 98% or more of the maximum profit.
urn:nbn:de:bvb:19-epub-17392-1
Keywords: C72; C78; L13; 330; brokers; simple mechanisms; percentage fees; real estate brokerage